Effects of mulching and irrigation levels on greenhouse capsicum (Capsicum annuum) - KUMARI, LAULINA; HASAN, MURTAZA; RANDHE, R D; SINGH, D K; SINGH, A K; ALAM, WASI (The Indian Journal of Agricultural Sciences, 2021)
The experiment was conducted during 2013-14, 2014-15 and 2015-16 under naturally ventilated greenhouse condition at Centre for Protected Cultivation Technology (CPCT), ICAR-Indian Agricultural Research Institute (IARI), New Delhi. The capsicum (Capsicum annuum L.) variety California Wonder was planted under colored plastic mulches (silver, yellow and black) and non-mulched (control) condition in combination with three levels of irrigation, viz. 100%, 80%, and 60% ETc.. The yield of capsicum was observed significantly higher under silver mulch (63-71.6 t/ha) followed by yellow mulch (60.04-67.04 t/ha) at 100% ETc and silver mulch (59.72-70.8 t/ha) at 80% ETc for three consecutive years. Growth parameters were significantly affected by different combination of treatments. The highest and lowest plant height (149.9 cm and 56.5 cm), leaf area (1.98 m2/m2 and 1.09 m2/m2) and total dry matter (120.4 g and 57 g) were observed under silver mulch with 100% and non-mulched with 60% ETc respectively during all the three years of experiment. Highest growth parameters were at par with silver mulch with 80% ETc treatment. Significantly higher crop water productivity (43.30-36.53 kg/m3) in silver mulch with 80 % ETc treatment was observed compared to other combination of treatments. The results revealed that, capsicum cultivation under silver coloured plastic mulch in the naturally ventilated greenhouse not only saved irrigation water but also enhanced yield, crop growth and crop water productivity at reduced level of irrigation (80% ETc). Silver colour plastic mulch was found to be best suitable for growing capsicum crop inside the naturally ventilated greenhouse.